Redesain Mesin Pengiris Singkong dengan Mekanisme Counterweight Gravity Feeder untuk Meningkatkan Produktivitas - Kusuma Dewi, Wiranti; Murnawan, Hery (Fakultas Teknik UMRI, 2025)
The Bojonegoro Cassava Chip MSME “Pak Ipul” faces production capacity constraints because its cassava slicing machine can only process 30 kg of cassava per hour. This study aims to redesign the cassava slicing machine by improving several key components such as the cassava feed chute, cutting blade, frame, motor + reducer, and drive system. The machine redesign is based on operator anthropometric data, referencing body dimensions such as elbow height while seated (64.46 cm), polyptal height (40.85 cm), knee height (50.33 cm), distance from elbow to fingertip (74.66 cm), and hip width while seated (45.15 cm), to create an ergonomic and safe design for the operator. The newly designed machine has a production capacity of 60 kg per hour, which is more efficient than the previous machine. The total cost of manufacturing the new machine is Rp 6,000,000, with raw material costs of Rp 3,900,000 and labor costs of Rp 2,100,000. Test results show a 50% increase in productivity, with a reduction in the time required to slice 75 kg of cassava from 2.5 hours to 1.25 hours. Depreciation analysis indicates that the new machine has a longer economic lifespan of 5 years, with annual depreciation of Rp 1,080,000, compared to the old machine, which only lasted 1 year. The Net Present Value (NPV) calculation for the new machine shows Rp 1,060,798.76, significantly higher than the old machine, which only generates Rp 24,235.45. Therefore, although the initial investment for the new machine is higher, it offers more significant long-term benefits and is worthwhile as an investment.